PENGGUNAAN MEDIA RODA PECAHAN UNTUK MENINGKATKAN HASIL BELAJAR PECAHAN SISWA KELAS IV SEKOLAH DASAR - Ahmad Faizin; Yuli Kurniawati; Inda Sari; RR Adetiyas Fara Ulil Muharromah; Ina Sulistiya; Nur Rokhmah; Lia Budi Tristanti (Lembaga Penelitian dan Pengabdian Kepada Masyarakat (LPPM) Universitas PGRI Jombang), 2026)
Low understanding of fraction concepts among elementary school students remains a common problem in mathematics learning. This condition is influenced by the abstract nature of fractions and the limited use of concrete learning media in schools. This Community Service program aimed to improve students’ learning outcomes and conceptual understanding of fractions through the implementation of Fraction Wheel Media. The method consisted of preparation, implementation, evaluation, and reporting stages. The preparation stage involved observation and interviews with teachers to identify learning problems. The implementation stage included developing the fraction wheel media, preparing usage guidelines, and assisting teachers in applying the media in classroom learning. Evaluation was conducted using pretests, posttests, and observation of students’ learning activities. The results showed a significant improvement in students’ learning outcomes, indicated by an increase in mastery learning percentage from a low initial condition to more than 75% after using the media. In addition, students demonstrated higher motivation, participation, and enthusiasm during learning activities. Teachers also gained new experiences in managing manipulative-based learning. Therefore, the fraction wheel media is effective as an alternative mathematics learning medium for fraction topics and has strong potential for sustainable implementation.